The business of music - Talbot, Michael, 1943- (Liverpool Music Symposium (Series), 2002)
Is business, for music, a regrettable necessity or a spur to creativity? Are there limits to the influence that economic factors can or should exert on the musical imagination and its product? In the eleven essays contained in this book the authors wrestle with these questions from the perspective of their chosen area of research. The range is wide: from 1700 to the present day; from the opera house to the community centre; from composers, performers and pedagogues to managers, publishers and lawyers; from piano miniatures to folk music and pop CDs. If there is a consensus, it is that music se.